(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The problems of determining and eliminating the root causes of the persecution of individuals and legal entities for their mistakes and their elimination are highlighted. If these problems are not eliminated, new errors, tax evasion, and underreporting of income in the tax base may occur, which require a scientific approach to eliminate, prevent, or eliminate. Based on the urgency of the problems, the main essence of our research is the introduction of effective mechanisms aimed at reducing the impact of violations on the formation of state budget revenues, and the creation of systematic management of the use of such mechanisms.